Hormonal and type-dependent adhesion of group B streptococci to human vaginal cells. - Botta, G A (1979)
Adhesion of group B streptococci to epithelial cells of the human vagina proved to be type dependent and to fluctuate during the menstrual cycle with a maximum near the time of ovulation. Oral contraception completely abolished the observed cyclic changes. Reduced serum levels of luteinizing hormones (less than 5 mIU/ml) and of follicle-stimulating hormone (less than 10 mIU/ml) were associated with a 10-fold reduction in adhesion of B streptococci to vaginal cells.